2018
DOI: 10.1002/anie.201802277
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Oxidation of Lithium Carbonate Generates Singlet Oxygen

Abstract: Solid alkali metal carbonates are universal passivation layer components of intercalation battery materials and common side products in metal‐O2 batteries, and are believed to form and decompose reversibly in metal‐O2/CO2 cells. In these cathodes, Li2CO3 decomposes to CO2 when exposed to potentials above 3.8 V vs. Li/Li+. However, O2 evolution, as would be expected according to the decomposition reaction 2 Li2CO3→4 Li++4 e−+2 CO2+O2, is not detected. O atoms are thus unaccounted for, which was previously ascri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
276
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 251 publications
(294 citation statements)
references
References 44 publications
14
276
0
4
Order By: Relevance
“…have studied the reactivity of 0.1 M LiClO 4 in ethylene glycol dimethylether (DME) electrolyte with singlet oxygen, photochemically generated with a photosensitizer . It has been shown that oxidation of Li 2 O 2 and also Li 2 CO 3 results in the production of 1 O 2 detected by the decrease in the fluorescence intensity of 9,10‐dimethylanthracene (DMA) due to its specific reaction with singlet oxygen, leading to the formation of an endoperoxide . However, fluorescence quenching of DMA has not always been unambiguously observed during oxygen reduction in aprotic solvents containing lithium, although the detection of the endoperoxide at high DMA concentrations revealed the formation of 1 O 2 during Li‐O 2 cell discharge .…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…have studied the reactivity of 0.1 M LiClO 4 in ethylene glycol dimethylether (DME) electrolyte with singlet oxygen, photochemically generated with a photosensitizer . It has been shown that oxidation of Li 2 O 2 and also Li 2 CO 3 results in the production of 1 O 2 detected by the decrease in the fluorescence intensity of 9,10‐dimethylanthracene (DMA) due to its specific reaction with singlet oxygen, leading to the formation of an endoperoxide . However, fluorescence quenching of DMA has not always been unambiguously observed during oxygen reduction in aprotic solvents containing lithium, although the detection of the endoperoxide at high DMA concentrations revealed the formation of 1 O 2 during Li‐O 2 cell discharge .…”
Section: Figurementioning
confidence: 99%
“…In the present communication we disclose new experimental evidence of the formation of singlet oxygen during oxygen reduction on carbon electrodes in LiTFSI in DMSO by following the fluorescence decay of DMA during ORR chronoamperometry using an electrochemical fluorescence cell without stirring. The experimental setup is similar to that described in Freunberger's papers but stirring of the liquid electrolyte was avoided intentionally …”
Section: Figurementioning
confidence: 99%
“…If all Li 2 CO 3 in each sample were completely oxidized to evolve CO 2 , this oxidation process would account for 20% (pristine) and 37% (Ta-doped) of the total CO 2 evolved during the first delithiation of each respective material, implying that electrolyte degradation accounts for a portion of CO 2 evolved. Further studies are necessary to fully understand the origin of CO 2 evolution for these materials, as the presence of Li 2 CO 3 can clearly affect the stability of the electrolyte at high voltages 33 . Nevertheless, our DEMS results clearly confirm that Ta-doping effectively reduces the evolution of oxygen from the oxide lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Tracing missing oxygen is the key step to explore the oxidation mechanism of Li 2 CO 3 . The ongoing pathway of O 2 has been proposed to form O 2 − (Equation ) or 1 O 2 (Equation ) . These highly reactive species induce electrolyte decomposition, resulting in the serious degradation of battery rechargeability.LiCO4+3Li++CO2+3normaleLi2CO3left2normalLi2normalCO34normalLi++4normale+2normalCO2+normalO2 (E° = 3.82 V vs normalLi/Li+)left2normalLi2normalCO3+2C2normalLi++4normale+3normalCO2 (E° = 2.80 V vs normalLi/Li+)2Li2CO34Li++3normale+2CO2+normalO22Li2CO34Li++4normale+2…”
Section: Other Energy Carriersmentioning
confidence: 99%